PENGARUH PEMBIAYAAN BERAKAD MUDHARABAH, MUSYARAKAH DAN MURABAHAH TERHADAP PROFITABILITAS (Studi Kasus pada Bank Umum Syariah Di Indonesia Tahun 2011-2017) - Fitriyatus Sa’adah; Jeni Susyanti; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to examine and analyze the effect of mudharabah, musyarakah and murabahah financing on profitability in sharia commercial banks in Indonesia in 2011-2017 both partially and jointly. Population is all public banks. Data collection goes through Indonesia as many as 12 while a sample of 5 matches the existing criteria. Data analysis in this study using SPSS version 16. The sampling technique using purposive sampling and data testing techniques used in this study include descriptive tests, normality tests, classic assumption tests and multiple linear regression analysis, autocoleration test, heterocedasticity test, simultaneous and partial test.The results of the analysis show that partially financing with mudharabah, musyarakah and murabahah funds does not have a significant effect on profitability performance. Whereas together or simultaneously shows that financing with mudharabah, musyarakah and murabahah influences significantly on profitability.Keywords: Mudharabah, Musyarakah, Murabahah and Profitability Financing